Growth and Characterization of Sr2RuO4 and Sr2RhO4 - Mortimer, Kevin (My University, 2014)
We report on the growth and characterization of strontium ruthenate (214) (Sr2RuO4) and strontium rhodate (214) (Sr2RhO4) in efforts to test their agreement with Landau-Fermi liquid theory using optical measurements. We begin by reviewing the theory of Landau-Fermi liquids and the frequency and temperature dependent conductivities. We review existing work on both Sr2RuO4 and Sr2RhO4 including evidence of agreement with Landau-Fermi liquid theory. We also describe optical floating zone crystal growth and the exact procedures we used to prepare samples of both Sr2RuO4 and Sr2RhO4 via optical floating zone. The resulting Sr2RuO4 crystals were characterized using AC susceptibility measurements and Sr2RhO4 by powder diffraction, single crystal diffraction, and SQUID magnetization measurements. Finally, early optical reflectivity measurements at low temperatures are presented.
Growth and Characterization of Strontium Ruthenate (214) and Strontium Rhodate (214)
With reference to some figures reproduced in this thesis: "Readers may view, browse, and/or download material for temporary copying purposes only, provided these uses are for noncommercial personal purposes. Except as provided by law, this material may not be further reproduced, distributed, transmitted, modified, adapted, performed, displayed, published, or sold in whole or part, without prior written permission from the American Physical Society."
Keywords: crystal growth; characterization; optical spectroscopy; sr2ruo4; sr2rho4; powder diffraction; single crystal diffraction; squid; ellipsometry; optical floating zone